URGENSI PENDIDIKAN NILAI-NILAI KARAKTER RABBANI BAGI GENERASI DIGITAL NATIVE - Suriana, Suriana (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The digital native in their daily life coexists a lot and takes advantage of time with digital technology. Therefore, to eliminate various negative impacts, both physically, psychologically, socially, religiously and even in character, requires character education that leads them to become the rabbaniyyun generation who are able to filter themselves in facing the digital world that is pouring over their lives. This library research study found appropriate character education values to be instilled in digital natives, namely rabbani characters. A character that God wants in humans listed in QS. Ali Imran (3): 79, which forms the basis of rabbani character education. The digital native who are rabbaniyyun are keen to learn useful knowledge, teach it to others, and put their knowledge into practice